Investigation of the mechanistic basis of N,N-dimethylformamide toxicity. Metabolism of N,N-dimethylformamide and its deuterated isotopomers by cytochrome P450 2E1 - Mráz, Jaroslav; Jheeta, Parmjit; Gescher, Andreas; Hyland, Ruth; Thummel, Kenneth; Threadgill, Michael D (Chemical research in toxicology, 1993)
Dimethylformamide (DMF) is an industrial solvent with hepatotoxic properties. The toxicity of DMF has been associated with its metabolism to S-(N-methylcarbamoyl)glutathione (SMG). The major urinary metabolite of DMF is N-(hydroxymethyl)-N-methylformamide (HMMF). HMMF undergoes oxidation in the formyl moiety, possibly via the intermediacy of its hydrolysis product N-methylformamide (NMF), and the reactive intermediate thus generated reacts with glutathione to yield SMG. Experiments were conducted to elucidate enzymatic details of the metabolism of DMF. Generation of HMMF from DMF in microsomes from rats which had received acetone, an inducer of cytochrome P450 2E1, was increased by 175% over that observed in control microsomes. In liver microsomes from 4 humans the metabolism of DMF to HMMF was inhibited by a monospecific antibody against rat liver P450 2E1, and the metabolic rates were correlated with those of NMF to SMG, a process known to be mediated via P450 2E1. DMF was also metabolized by purified rat liver P450 2E1. The kinetic parameters which characterize the metabolism of DMF or its deuterated isotopomers to the respective HMMF isotopomers, of HMMF to SMG and of NMF to SMG in liver microsomes, were computed from Eadie-Hofstee plots. The affinity of DMF for the metabolizing enzyme in rat liver microsomes is considerably higher (apparent Km = 0.20 mM) than that of NMF (Km = 4.28 mM) or of HMMF (Km = 2.52 mM). The respective values observed with human microsomes are very similar. The apparent Km values for the N-methyl oxidation of N,N-dimethyldeuterioformamide ([2H1]DMF) and N,N-bis(trideuteriomethyl)formamide ([2H6]DMF) in rat microsomes are 0.14 and 0.21 mM, respectively. The apparent Vmax for the oxidation of [2H1]DMF is similar to that computed for DMF, and the Vmax for [2H6]DMF is less than half of that computed for DMF. The kinetic deuterium isotope effect (KDIE) on DMF metabolism was determined in incubations with rat microsomes in three ways: (i) the noncompetitive intermolecular KDIE by the ratio of Vmax/Km for DMF to Vmax/Km for [2H6]DMF, (ii) the competitive intermolecular KDIE as the quotient of metabolic products HMMF to N-(hydroxydideuteriomethyl)-N-(trideuteriomethyl)formamide in incubations of DMF together with [2H6]DMF, and (iii) the intramolecular KDIE as the quotient of the ratio of N-(hydroxymethyl)-N-(trideuteriomethyl)formamide to N-(hydroxydideuteriomethyl)-N-methylformamide generated from N-(trideuteriomethyl)-N-methylformamide ([2H3]DMF). The respective values were found to be (i) 2.4, (ii) 5.0, and (iii) 5.2. DMF inhibited the oxidation of NMF or HMMF to SMG.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: dimethylformamid; potkani Sprague-Dawley; Dimethylformamide; techniky in vitro; Rats, Sprague-Dawley; Humans; systém (enzymů) cytochromů P-450; zvířata; Rats; isomerie; mužské pohlaví; chromatografie plynová; oxidace-redukce; Kinetics; amidy; krysa rodu Rattus; Isomerism; kinetika; Animals; lidé; jaterní mikrozomy; Cytochrome P-450 Enzyme System; Amides; Male; In Vitro Techniques; Oxidation-Reduction; Chromatography, Gas; Microsomes, Liver